Pemanfaatan Media Sosial sebagai Sarana Pemasaran Hasil Pertanian Kelompok Tani Manekat Kelurahan Nonbes - Panis, Isabel Coryunitha; Klaudia, Maria Vinsia; Inosentia, Yohanesta Paula; Takoy, Agatny -; Banda, Bernadina Dupa (Universitas Veteran Bangun Nusantara, 2023)
Social media is one of the instant media that is currently used by almost all groups to interact with each other online or indirectly without being limited by space and time. In this era of globalization, social media is intended as a forum for its users to easily adapt, share and exchange information. Social media is a facility for building relationships with consumers directly. Through social media, consumers can communicate directly about the products being sold. As a seller, you can directly provide feedback to consumers interactively and quickly. Training on the use of social media as a marketing tool conducted by Widya Mandira Catholic University's Thematic Real Work Lectures – Community Empowerment Learning (KKNT-PPM) is one form of activity carried out by students in improving the community's economy in facing the Economic Recession.